Penyelesaian Perselisihan Pemutusan Hubungan Kerja Yang Memasuki Purnatugas Menurut Undang – Undang Nomor 11 Tahun 2020 Tentang Cipta Kerja - Indi Nuroini (Deposisi: Jurnal Publikasi Ilmu Hukum, 2023)
This study aims to clearly describe the regulation of regulations that examine changes in the Employment Copyright Act, the legal consequences that can be caused to companies if they do not provide severance pay at the time of Termination of Employment and Government Regulation no. 35 of 2021. This type of research uses a normative juridical research model. Based on the Employment Act, a person who has retired, his rights and severance pay must be paid in accordance with the mandate of Article 156 paragraph (1). The results of this study are 1). based on several legal provisions as mentioned above, we can conclude that the retirement age in 2022 is at the age of 58 (fifty eight) years, 2). the current regulation regarding layoffs does not have to go through the determination of the Industrial Relations Court (PHI), the Company only needs to inform the workers of the intent and reason for the layoffs. If the worker refuses to be laid off, the worker can propose bipartite negotiations to the company and if a meeting point does not occur, mediation can be carried out, up to a settlement at the PHI, 3). different arrangements between the Manpower Act and the Job Creation Act. Among them is the amount of entitlement to severance pay. In the Manpower Act, a person who retires gets a severance pay amount of 2x (twice) the provisions of Article 156. While in the Employment Act it is 1.75 (one point seventy-five) from Articles 156, 4). criminal law provisions in the Copyright Act, if the employer does not provide severance pay in accordance with applicable legal provisions to workers who have been laid off due to entering retirement age. This is not regulated in the manpower law which is more civil in nature in terms of resolving disputes over layoffs.